2022
DOI: 10.3390/molecules27103108
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Proteomics Identifies Interaction Partners and Defines Novel Insights into the Function of the Adhesion GPCR VLGR1/ADGRV1

Abstract: The very large G-protein-coupled receptor 1 (VLGR1/ADGRV1) is the largest member of the adhesion G-protein-coupled receptor (ADGR) family. Mutations in VLGR1/ADGRV1 cause human Usher syndrome (USH), a form of hereditary deaf-blindness, and have been additionally linked to epilepsy. In the absence of tangible knowledge of the molecular function and signaling of VLGR1, the pathomechanisms underlying the development of these diseases are still unknown. Our study aimed to identify novel, previously unknown protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(58 citation statements)
references
References 121 publications
(156 reference statements)
4
52
0
Order By: Relevance
“…To monitor the Ca 2+ flux in the two organelles, we made use of genetically encoded Ca 2+ indicators targeted to ER, (G-CEPIA1er) and mitochondria (CEPIA2mt) [ 17 ]. We previously showed that primary astrocytes from mouse brain are well suited for studies of VLGR1 in cells [ 3 , 9 ]. Both Ca 2+ indicators were transfected into primary brain astrocytes, derived from Vlgr1 del7TM or wild-type control mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To monitor the Ca 2+ flux in the two organelles, we made use of genetically encoded Ca 2+ indicators targeted to ER, (G-CEPIA1er) and mitochondria (CEPIA2mt) [ 17 ]. We previously showed that primary astrocytes from mouse brain are well suited for studies of VLGR1 in cells [ 3 , 9 ]. Both Ca 2+ indicators were transfected into primary brain astrocytes, derived from Vlgr1 del7TM or wild-type control mice.…”
Section: Resultsmentioning
confidence: 99%
“…( A ) VLGR1 protein domain composition: VLGR1 molecules consist of a C-terminal fragment (CTF) and a N-terminal fragment (NTF) which result from the cleavage at the highly conserved GPCR proteolytic site (GPS) in the GAIN (autoproteolysis-inducing) domain positioned next to the seven-span transmembrane domain (TM). After autoproteolytic cleavage the first 11 amino acids of VLGR1_CTF, the so-called Stachel peptide, can act as a tethered internal agonist for receptor activation [ 3 ]. The extracellular domain (ECD) of VLGR1b contains numerous Ca 2+ binding calcium exchanger β motifs (Calx-β), seven epilepsy-associated/Epitemptin-like (EAR/EPTP) repeats and a pentaxin/laminin G-like domain (LamG/PTX).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that autocleavage at GPS exposes the short so-called "spike" sequence at the N-terminal end of CTF, which serves as a bound agonist to activate aGPCRs 3,4 . In VLGR1, we have recently identified 11 amino acids that act as the "Stachel" peptide 5 . Furthermore, we also found evidence that this activation induces a switch from Gs-to Gi-mediated signalling of VLGR1.…”
Section: Introductionmentioning
confidence: 99%
“…Because knowledge of potential interaction partners often provides reliable insights into the function of proteins, we have searched for potential partners of VLGR1 by an affinity proteomics capture approach to provide insights into its cellular functions 5,12 . This strategy has recently enabled us to unravel valuable new insights into the downstream receptor signalling of VLGR1 5 , its participation as a metabotropic membrane mechanoreceptor in the regulation of focal adhesion during cell migration 13,14 , and its role in the function of internal membrane compartments, such as the mitochondria-associated membranes (MAMs) of the endoplasmic reticulum (ER) 15 .…”
Section: Introductionmentioning
confidence: 99%